THE INFLUENCE OF IMPLEMENTING NON-FORMAL SUPERVISION ON TEACHER PERFORMANCE IN SUSTAINABLE PROFESSIONAL DEVELOPMENT AT STATE JUNIOR HIGH SCHOOLS OF MAKASSAR - Jihad, Siti Ariati; Syamsudduha, St.; Yahya, Muhammad (Jurnal Diskursus Islam, 2021)
The aims of this study are to: (1) describe the implementation of non-formal supervision at state Junior High Schools of Makassar (2) describe teacher performance in Continuing Professional Development (CPD) at state Junior High Schools of Makassar (3) describe the effect of implementing non-formal supervision on teacher performance in Continuous Professional Development. This research is quantitative research with the type of ex-post-facto research. The approach used is a sociological, psychological, and quantitative approach. The population in this study was 40 State Junior High schools (SMPN) in Makassar. The samples in this study were SMPN 29 Makassar that included 15 teachers, and SMPN 8 Makassar, with 15 teachers who had been certified using a multistage random sampling technique to assess performance in CPD and principals to determine the implementation of non-formal supervision. The results obtained in this study indicate that: (1) The results of the descriptive analysis of non-formal supervision at SMPN Makassar are in the Very High category with a frequency of 15 people from 30 samples and or 50%. 2) The results of the descriptive analysis The assessment of teacher performance in Continuous Professional Development is in the Very High category with a frequency of 11 people out of 30 samples or 36.66%. (3) The results of the inferential analysis comparing ttable and tcount, it turns out that tcount = 2.137 > ttable = 2.048, then Ho is rejected and H1 is accepted so that it is known that there is a significant effect of non-formal supervision (X) and teacher performance in Continuing Professional Development (Y) at SMPN Makassar. The implications of this research are: (1) the implementation of non-formal supervision at SMPN Makassar, in general, can be applied and maintained. (2) Teacher Performance Assessment in Sustainable Professional Development, in general, can be applied and improved again and can be used as a model for other schools in the application of supervision.